2010
DOI: 10.1073/pnas.1001749107
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between decidual NK and CD14 + myelomonocytic cells results in induction of Tregs and immunosuppression

Abstract: Regulatory T cells (Tregs) are thought to play a major role in pregnancy by inhibiting the maternal immune system and preventing fetal rejection. In decidual tissues, NK cells (dNK) reside in close contact with particular myelomonocytic CD14 + (dCD14 + ) cells. Here we show that the interaction between dNK and dCD14 + cells results in induction of Tregs. The interaction is mediated by soluble factors as shown by transwell experiments, and the prominent role of IFN-γ is revealed by the effect of a neutralizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
194
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(204 citation statements)
references
References 56 publications
4
194
2
4
Order By: Relevance
“…Reflecting remarkable plasticity, CD14 1 myelomonocytic cells efficiently respond to various environmental stimuli, particularly the semi-allograft, which might induce the differentiation of these cells in a tissue-specific manner for immune regulation and host defense responses 2,[27][28][29] . Studies have shown that CD14 1 myelomonocytic cells, which intimately contact the embryo allograft, displayed a unique ability to promote immunotolerance via the induction of Tregs 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting remarkable plasticity, CD14 1 myelomonocytic cells efficiently respond to various environmental stimuli, particularly the semi-allograft, which might induce the differentiation of these cells in a tissue-specific manner for immune regulation and host defense responses 2,[27][28][29] . Studies have shown that CD14 1 myelomonocytic cells, which intimately contact the embryo allograft, displayed a unique ability to promote immunotolerance via the induction of Tregs 2 .…”
Section: Discussionmentioning
confidence: 99%
“…As major leukocyte subsets, CD14 1 myelomonocytic cells increase after embryo implantation and closely contact fetal trophoblast cells. Owing to their remarkable plasticity, cytokine production, and functional properties, different subtypes of maternal CD14 1 myelomonocytic cells perform multiple disparate functions during early pregnancy [2][3][4][5] . Maternal CD14 1 myelomonocytic cells have gained increasing attention, as these cells play a multifaceted role during early pregnancy; however, the definition of new subsets and the contribution of each population to the immunological microenvironment of pregnancy are just beginning to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…39 Differentiation of CD34 1 cells into CD56 bright NK cells has also been demonstrated in other tissues, such as the lymph nodes. 40 Recently, studies in mice have described two waves of distinct hematopoietic cells in the fetal thymus with potential to develop into NK cells. 65 The different hypotheses regarding the origin of dNK cells are not mutually exclusive.…”
Section: Human Nk Cellsmentioning
confidence: 99%
“…Moreover, iDCs are able to affect the cytokine profile of dNK cells by inducing the IFN-c release of dNK cells. 40 In turn, dNK-derived IFN-c induces the expression of some suppressive molecules, such as indoleamine 2,3-dioxygenase, in decidual DCs, thereby promoting the induction of regulatory T cells in the human decidua (Figure 2b). 60 Similarly, dNK cells are also able to influence DC function during pregnancy.…”
Section: Nk/dc Liaison At the Fetomaternal Interfacementioning
confidence: 99%
“…18 It was reported that the interaction of dNK and CD14 1 cells lead to CD4 1 CD25 1 regulatory T (Treg) cells induction and immunosuppression. 19 Moreover, a recent study showed that CD56 bright CD27 1 NK cells promote immune tolerance and successful pregnancy through IFN-c secretion, thereby inhibiting inflammatory TH17 cells. 20 Similar to the TH1 and TH2 subsets of CD4 1 T cells, NK cells are divided into NK1 and NK2 subpopulations based on their cytokine secretion profiles.…”
Section: Introductionmentioning
confidence: 99%